DPCM: a method for modelling and analysing design process changes based on the Applied Signposting Model. Issue 11 (1st November 2016) - Shapiro, Daniel; Curren, Matthew D.; Clarkson, P. John
ABSTRACT: Research on changes in design has focused on changes in the product domain. However, because the product's design process may change as well, this article suggests a comprehensive method to support modelling and analysing changes in the process domain (DPCs). After developing the concept for the Design Process Change Method (DPCM) based on requirements derived from literature and industrial practice, the DPCM is detailed and computationally implemented using the framework of the Applied Signposting Model. The DPCM enables design teams to conduct various useful analyses, which enhance the understanding of DPC effects on process performance, support process execution through suggesting mitigating reactions to DPCs, and support process planning through identifying and prioritising the 'right' DPCs. The method's application is demonstrated based on the fan sub-system preliminary design process of Rolls-Royce PLC.